Increased Attractiveness and Shelf Life of Siamese Tangerines (Citrus Nobilis L.) Using Various Palmitic, Stearic, and Oleic Acid Emulsions and Mixtures - Ni Luh Putu Putri Setianingsih; Ni Made Suaniti; I Gede Putu Wirawan (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Along with the growing number of people, the need for food is also growing. Citrus nobilis l is one of the many well-known fruits. Citrus nobilis L, both in its fresh and processed forms, is easily broken if it is not treated correctly. This study hopes to make things look better and save power simultaneously by coming up with different emulsions. Palmitic acid, stearic acid, oleic acid, and a mix make the slurry. Organoleptic study of Citrus nobilis L., vitamin C content, water content, and identification of compounds using Gas Chromatography-Mass Spectrometry (GC-MS). Evaluation of organoleptic analysis test done by hedonic test (colour, smell, texture, taste, and general acceptance) and test scoring (colour, texture). A combination of palmitic, stearic, and oleic acids in an emulsion will make tangerine fruit look better and last longer. How vitamin C and water are measured and analyzed affects different emulsions. When citrus fruits are treated with palmitic, stearic, and oleic acid solutions, the lowest quality drops to 14.4851 mg of vitamin C per 100 grammes and 91.8401% water. The total amount of volatile compounds in fruit orange conjoined DL-Limonene has many different areas of volatile compounds in each treatment emulsion.